Organic polymer materials in the space environment. (May 2016) - Chen, Jun; Ding, Nengwen; Li, Zhifeng; Wang, Wei
Abstract: The space environment is a complex environment full of microgravity, high vacuum, high and low temperature, strong radiation and plasma. Polymers used in the space environment will inevitably experience aging and degradation which result in changes of the material mechanics, physics and chemical properties, until they lose usefulness. To make a material that can be used for a long time and whose performance is not changed in the space environment, its ability to resist environmental factors must be excellent. Therefore, this paper provides an introduction to the harmful conditions in the space environment and their effects on the polymers, also it reviews the aging mechanisms of the adhesives used in the space environment and the effect of thermal cycling, stress, electromagnetic radiation and ionizing particles on the properties of polymers and optical devices, to provide the reference basis for selection, modification and reliability analysis of materials used in the space environment.